2009
DOI: 10.5194/aab-52-265-2009
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of endoparasites in heifers imported to Poland from the Netherlands (Short Communication)

Abstract: Prevalence of gastrointestinal parasites was studied in 106 heifers imported to Poland from the Netherlands. Prevalence of gastrointestinal nematodes and Eimeria protozoans was determined from coproscopic examinations using Willis-Schlaf flotation. The species composition of coccidia was determined from morphological characters and the time of oocyst sporulation. Fluke liver eggs were detected by decantation. The study showed the mean prevalence of Eimeria protozoans in the heifers imported from the Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…Other species of Eimeria viz . E. bukidnonensis , E. subspherica , E. auburnensis , E. alabamensis and E. ellipsoidalis were also recorded in cattle with varying percentage which is in conformity with the reports from Brazil [ 1 ], Pakistan [ 3 ], Hungary [ 20 ], India [ 21 ], Poland [ 22 ], and China [ 23 ]. The variation in prevalence of Eimeria spp.…”
Section: Resultssupporting
confidence: 87%
“…Other species of Eimeria viz . E. bukidnonensis , E. subspherica , E. auburnensis , E. alabamensis and E. ellipsoidalis were also recorded in cattle with varying percentage which is in conformity with the reports from Brazil [ 1 ], Pakistan [ 3 ], Hungary [ 20 ], India [ 21 ], Poland [ 22 ], and China [ 23 ]. The variation in prevalence of Eimeria spp.…”
Section: Resultssupporting
confidence: 87%
“…2). Pilarczyk et al (25,26) showed that the course of parasitic invasion depends, first of all, on climatic and environmental conditions. The results obtained in our study confirm the observations made by other authors (3,4,10,11,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Of many factors causing diseases, parasites deserve a particular attention. Parasitoses are the most common illness of ruminants (1, 3, 10, 11, 13, 18, 22, 23, [25][26][27]. They cause large losses resulting mainly from the reduction in animal condition, productivity, and resistance to diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research performed in other countries has revealed prevalence rates of Eimeria spp. varying from 17.9% to 93% in Poland (Pilarczyk et al 2000;Klockiewicz et al 2007;Pilarczyk et al 2009), 33% in Hungary (Farkas et al 2007), 22.6% and 33.3% in Brazil (Almeida et al 2011;Poscoti-Bruhn et al 2011), 35% to 47.1% in China (Yu et al 2011;Dong et al 2012), 50% in Pakistan (Nisar-Khan et al 2013), 22.7% and 68% in Ethiopia (Abebe et al 2008;Dawid et al 2012), 20%, 68% and 75% in Turkey (Arslan and Tuzer 1998;Cicek et al 2007;Nalbantoglu et al 2008), 29%, 50% and 52% in South Africa (Matjila and Penzhorn 2002), and 35% in Tanzania (Chibunda et al 1997). The rate was reported to be 21.3% and 18% to 50% in the Kurdistan and East-Azerbaijan provinces of Iran (Yakhchali and Gholami 2008;Yakhchali and Zarei 2008;Davoudi et al 2011).…”
Section: Discussionmentioning
confidence: 99%